2018
DOI: 10.3389/fpls.2018.01613
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Synthetic Chemical Inducers of Plant Immunity

Abstract: Different from the conventional biocidal agrochemicals, synthetic chemical inducers of plant immunity activate, bolster, or prime plant defense machineries rather than directly acting on the pathogens. Advances in combinatorial synthesis and high-throughput screening methods have led to the discovery of various synthetic plant immune activators as well as priming agents. The availability of their structures and recent progress in the mechanistic understanding of plant immune responses have opened up the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 134 publications
(157 reference statements)
0
47
0
5
Order By: Relevance
“…Taking advantage of the plant-induced resistance against harmful organisms could be a promising alternative strategy for pests and pathogens management in the field [5,6]. A chemical elicitor is one of the most powerful tools in this domain [9,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the plant-induced resistance against harmful organisms could be a promising alternative strategy for pests and pathogens management in the field [5,6]. A chemical elicitor is one of the most powerful tools in this domain [9,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more evidence demonstrated that the exogenous application of phytohormones could elicit plant resistance against herbivores or pathogens either in herbs or in woody plants [4]. In recent years, the analogues of these phytohormones modulating the corresponding pathways have been investigated by researchers [5,6]. Several chemical elicitors have been commercially used in greenhouse disease control, such as benzo (1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester (BTH), 2,6-dichloroisonicotinic acid (INA), β-aminobutyric acid (BABA), tiadinil (TDL), and pyraclostrobin [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Bunlar başlıca; SA türevleri, isonikotinik asit türevleri (INA), thiadiazole ve isothiazole türevleri, JA analoğu ve β-aminobutirik asit (BABA)'tir. "Biyolojik bitki immunitesi uyarıcı moleküller" ise; bir patojen ile konukçusu arasındaki etkileşim sırasında üretilen aktif küçük moleküllerdir (Zhou and Wang, 2018;Tosun ve Yiğit, 2012). Biyolojik aktif moleküller; metabolitleri, oligosakkaritleri, glikoproteinleri, glikopeptitleri, proteinleri, polipeptitleri, lipitleri ve diğer hücresel bileşenleri içerir (Dewen et al 2017).…”
Section: Bitki Hastalıklarının Entegre Yönetiminde Bitki İmmunitesi Uunclassified
“…Basit olarak biyolojik immunite uyarıcılarının yapılarını taklit ederek bitki immunitesini uyarabilmektedirler. Biyolojik bitki uyarıcıları ile yapısal olarak akraba da olmayabilirler ve savunma sinyal bileşenlerinin bir alt kümesini hedefleyebilirler (Zhou and Wang, 2018).…”
Section: B Sentetik Bitki İmmunitesi Uyarıcı Kimyasallarunclassified
See 1 more Smart Citation